(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Emotional intelligence has existed in various forms for several decades. It was introduced in the early 1990s by psychologists Peter Salovey and John D.Mayer , and since then, educators, practitioners and researchers have recognized the significance of it in promoting academic success and personal development between students. The first part of this article discusses what emotional intelligence is, its potential benefits, and how it can be advantageous in education. The second part presents a survey conducted by Schutte, Malouff, Thorsteinsson, Bhullar, and Rooke in 2018 in order to see impact of emotional intelligence for academic performance and demonstrates certain spheres of education which emotional intelligence can be crucial and immense.